NHC-catalyzed [4+2] cycloaddition reactions for the synthesis of 3′-spirocyclic oxindoles via a C–F bond cleavage protocol. Issue 13 (18th December 2017) - Yan, Jun; Shi, Kuangxi; Zhao, Chengtao; Ding, Liyuan; Jiang, Shengsheng; Yang, Limin; Zhong, Guofu
Abstract : A chiral NHC-catalyzed cycloaddition of γ-fluoroenals is developed. The nucleophilic γ-carbon generated via C–F bond cleavage undergoes highly enantioselective cycloaddition (up to >99% ee) to isatins and provides 3′-spirocyclic oxindoles in good yields (up to 91%). Abstract : A chiral NHC-catalyzed cycloaddition of γ-fluoroenals is developed. The nucleophilic γ-carbon generated via C–F bond cleavage undergoes highly enantioselective cycloaddition (up to >99% ee) to isatins and provides 3′-spirocyclic oxindoles in good yields (up to 91%).